Revolutionary Cuba : a history - Martínez-Fernández, Luis, 1960- (University Press of Florida, 2014)
This is a comprehensive, interpretative history of the Cuban Revolution, from the time of Batista's 1952 coup to the present. The book offers a balanced perspective on the revolution by recognizing its accomplishments, pointing out its shortcomings, and denouncing its excesses.